A review of hatchery techniques of red tilapia (Oreochromis niloticus) at UPT of Freshwater Aquaculture Fisheries (PBAT) Pasuruan - Al Ghozali, Ashil Falih Kes Foh; Gunawan, Doddy; Sawiji, Asri (UIN Sunan Ampel Surabaya, 2021)
Red tilapia (Oreochromis niloticus) has its advantages compared to other cultivated fish. Namely, it can proliferate, is easy to breed, and is efficient for feeding. Besides, these fish can also tolerate changes in the aquatic environment. With these advantages, this fish is increasingly popular among cultivators. The need for tilapia fish seeds is increasing every year. The UPT of Freshwater Aquaculture Fisheries (PBAT) of Pasuruan Regency is one of the superior seed supply units for fisheries in East Java. The superior commodity is tilapia fish seeds. The purpose of this research is to know hatchery techniques for Red Tilapia (Oreochromis niloticus) at UPT PBAT Pasuruan Regency. The research was carried out directly through active participation in all Red Tilapia hatchery activities. The results are: Red tilapia hatchery at UPT PBAT Pasuruan Regency, uses natural spawning techniques with a male to female ratio of 1: 3. The spawning period is 21 days until harvest with two types of broodstocks, namely mature sires (2500-2700gr) and novice sires (300-500gr); The hatchery technique stages are media preparation, parent selection, spawning, larva harvesting, larva treatment, nursery, and seed harvesting; Water quality is still within the quality standard set by PP. 82 of 2001 with details of the average temperature of 29C, DO 7.7 mg / L, pH 8.325, and water depth of 50 cm.